A qualitative study exploring the clinical phenomenology and impact of hypersexuality in patients with Parkinson’s Disease - Natalie Tayim; Jalesh N. Panicker; Jennifer Foley; Caroline Selai; Walaa G. El Sheikh (Scientific Reports)
Abstract Hypersexuality (HS) is a complex yet underreported phenomenon in Parkinson’s disease (PD), profoundly impacting patients’ lives. This study aims to systematically investigate the clinical phenomenology and manifestations of HS using qualitative methodologies. This phenomenological qualitative research study employed semi-structured interviews to examine hypersexuality and its impact among nine English-speaking individuals with PD. Participants were recruited from clinical settings and met specific inclusion criteria, including clinically diagnosed PD, reported hypersexuality post-PD diagnosis, and no cognitive impairment. The study adhered to ethical standards, with written informed consent obtained from all participants. Nine patients with PD (six males, mean age 61.7 ± 13.3 years, and three females, mean age 64.3 ± 5.7 years) participated. The mean age of PD onset was 51.4 ± 12.5 years, while HS onset was 54.1 ± 11.5 years, ranging from 35 to 68 years. Eight of the nine patients were in monogamous relationships. Qualitative analysis revealed ten themes. Clinical manifestations included increased preoccupation with sex, heightened desire, and altered behaviors like risk-taking. Sexual practices varied, with increased urges not necessarily leading to more frequent sex with partners; instead, behaviors like masturbation and promiscuity were common. Emotional formulations ranged from negative to neutral, influenced by whether patients internalized or externalized their hypersexuality. Insight varied, with some patients viewing HS as natural and others seeing it as conflicting with their values. Control over HS was mixed, with efforts to manage behaviors influenced by personal or external factors. The impact on life was predominantly negative, affecting marital closeness, family dynamics, social interactions, work efficiency, and physical health. Patients perceived mostly negative feelings from their partners regarding HS. Stigma was significant, including personal shame, social concealment, and discomfort discussing HS with health professionals. Barriers to seeking help included communication deficits, professional neglect, and stigma. Despite challenges, patients expressed a desire for better guidance and open discussions with health professionals to manage HS. This study uncovered the profound impact of HS on various facets of life such as quality of life, work, and personal relationships, elucidating the emotional distress and societal challenges faced by patients. This preliminary study on hypersexuality in neurological disorders suggests multiple avenues for future research.